2023
DOI: 10.1001/jamanetworkopen.2023.40695
|View full text |Cite
|
Sign up to set email alerts
|

Survival Among Veterans Receiving Steroids for Immune-Related Adverse Events After Immune Checkpoint Inhibitor Therapy

Inga Van Buren,
Cecelia Madison,
Aimee Kohn
et al.

Abstract: ImportanceSystemic steroids are commonly used to manage immune-related adverse events (irAEs), but it remains unclear whether they may undermine immune checkpoint inhibitor (ICI) therapy outcomes. Few studies have assessed the impact of steroid timing and its association with continuation or cessation of ICI therapy.ObjectiveTo characterize how systemic steroids and steroid timing for irAEs are associated with survival in patients receiving ICI therapy.Design, Setting, and ParticipantsThis multicenter retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…However, unlike other irAEs, they tend to be irreversible, leading to a need for lifelong hormone supplementation [14,18,20]. The impact of corticosteroid therapy for irAEs on ICI efficacy is unclear; the organ system affected, the primary tumor type, as well as the timing and dose of systemic steroid therapy may be significant [21][22][23][24]. It has been suggested that the use of systemic corticosteroids is a poor prognostic factor independent of the use of ICIs; however, this has not been consistently shown in patients with LC [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike other irAEs, they tend to be irreversible, leading to a need for lifelong hormone supplementation [14,18,20]. The impact of corticosteroid therapy for irAEs on ICI efficacy is unclear; the organ system affected, the primary tumor type, as well as the timing and dose of systemic steroid therapy may be significant [21][22][23][24]. It has been suggested that the use of systemic corticosteroids is a poor prognostic factor independent of the use of ICIs; however, this has not been consistently shown in patients with LC [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, steroid timing for immune-related adverse events may be associated with survival in patients receiving immune checkpoint inhibitor therapy. In large multicenter retrospective cohort study (n=20163), systemic steroids for immune-related adverse events were associated with significantly improved survival compared with those who received steroids for other reasons or no steroid treatment (mOS, 21.3 versus 13.6 versus 15.8 months; P<0.001) (129). However, among those who received steroids for immune-related adverse events, early steroid use (<2 months after immune checkpoint inhibitor…”
Section: Dexamethasone Use Is a Prognostic Factor For Shorter Survivalmentioning
confidence: 99%
“…However, steroid timing for immune-related adverse events may be associated with survival in patients receiving immune checkpoint inhibitor therapy. In large multicenter retrospective cohort study (n=20163), systemic steroids for immune-related adverse events were associated with significantly improved survival compared with those who received steroids for other reasons or no steroid treatment (mOS, 21.3 versus 13.6 versus 15.8 months; P<0.001) ( 129 ). However, among those who received steroids for immune-related adverse events, early steroid use (<2 months after immune checkpoint inhibitor initiation) was associated with reduced relative survival benefit in comparison to later steroid use, regardless of immune checkpoint inhibitor continuation or cessation following steroid initiation (mOS after immune checkpoint inhibitor cessation, 4.4 versus 16.0 months; mOS after immune checkpoint inhibitor continuation, 16.0 versus 29.2 months; P<0.001) ( 129 ).…”
Section: Standard Therapy-related Immunosuppression In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation